The Effect of Activity, Liquidity, Profitability, And Solvency on Stock Prices and Implications on Firm Value: Pharmaceutical Industry Sub-Sector Companies - Sufyani, Mujibah A; Cahbana, Angga (MIX: JURNAL ILMIAH MANAJEMEN, 2024)
Objectives: This research aims to conduct a descriptive and verificative analysis of the condition of Activity Ratio, Liquidity, Profitability, Solvency, and Stock Price in the pharmaceutical industry on the Indonesia Stock Exchange from 2009 to 2020. Additionally, the study aims to identify and analyze the extent to which Activity Ratio, Liquidity, Profitability, and Solvency influence Stock Price and its implications on Firm Value. Quantitative data will be used to gather the necessary information for analyzing the relationships between these variables.Methodology: This study utilized a sample of 7 companies selected through purposive sampling, which involves choosing samples based on specific criteria. The data used for analysis is secondary data obtained from the annual reports available on the official website of the Indonesia Stock Exchange (IDX). The data analysis methods employed in this study include panel data regression analysis, multiple linear regression analysis, hypothesis testing, and determination coefficient analysis.Finding: The findings of the study revealed that when considered collectively, the Activity Ratio, Liquidity, Profitability, and Solvency variables had a significant impact on the Stock Price, as indicated by a coefficient of determination (R2) of 69.92%. Individually, the Activity Ratio exhibited a negative and significant influence on the stock price, while profitability demonstrated a positive and significant effect on the stock price. On the other hand, liquidity and solvency were found to have no significant effect on the stock price. Additionally, the study identified a significant relationship between Stock Price and Firm Value The results show that the company's activity (Activity Ratio), liquidity (Liquidity), profitability (Profitability), and solvency (Solvency) have a significant impact on stock prices. Companies with high activity levels, good liquidity, high profitability, and strong solvency tend to have higher share prices. This research provides an understanding of the factors that influence stock prices and can assist investors, financial analysts, and companies in making investment decisionsConclusion: The conclusions of this study are Activities measured by TATO, Liquidity measured by CAR, Profitability measured by ROA in pharmaceutical industry sub-sector companies for the 2009-2020 period tend to decrease, while Solvency measured by DAR and Firm Value in pharmaceutical industry sub-sector companies for the 2009-2020 period tends to increase,